The Implementation of The Social Role of Sociology Teachers in The Community (Study of Teachers in North Lombok) - Masyhuri, Masyhuri; Suud, Suud; Ilyas, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This research aims to describe the implementation of the social role of high school sociology teachers in North Lombok within the community and the influencing factors. This is a qualitative descriptive study. The research subjects are high school sociology teachers in North Lombok. The informants are community leaders in the areas where the research subjects reside. Data were collected using interview techniques, observation, and documentary study. Data analysis was conducted through qualitative analysis steps, including data reduction, data presentation, verification/conclusion drawing. The results of the research show that the implementation of the social role of high school sociology teachers in North Lombok in the community includes: (1) as leaders in the community, both formal leaders and informal leaders. Formal leaders serve as village heads, while informal leaders serve as heads of local community organizations, women's groups, and mosque/musalla construction committees. (2) as facilitators in finding donors to support public facility development. (3) as mediators connecting youth with local community leaders to communicate various programs initiated by the youth. (4) as initiators of various activities, including initiating the establishment of Islamic schools, initiating the creation of Quranic reading centers, initiating the renovation of mosques and musallahs, and initiating social service activities. (5) as participants, with sociology teachers actively participating in various community activities, such as community work groups, community cleanup, reforestation, social service activities, sports events, and local community competitions. Factors influencing the implementation of the social role of high school sociology teachers in North Lombok within the community include supporting factors and hindering factors. Supporting factors consist of family support and local community solidarity. Hindering factors include the busyness of the community with unpredictable work schedules and the relatively low level of education in the local community, which makes it challenging to build understanding and awareness among the local population.